Land Suitability Evaluation of Maize Crop in Tilamuta Ditrict of Boalemo Regency - Dunggio, Muhadjir; Nurdin; Purnomo, Sutrisno Hadi (International Journal of Technology and Education Research, 2026)
This study aims to determine the land suitability class and limiting factors for maize (Zea mays L.) in Tilamuta District, Boalemo Regency. The study will take place from August 2025 to September 2025 in Tilamuta District, Boalemo Regency. The method used in this study is the matching method, or matching between land characteristics and quality with the criteria for maize land suitability. The results of the analysis show that the actual land suitability for maize plants in Tilamuta District, Boalemo Regency, is in the marginal suitability class (S3) and is spread across all land units. This condition is influenced by several main limiting factors, namely low nutrient availability, rainfall, soil nutrient retention capacity, slope gradient, and erosion hazard levels. However, for potential land suitability, the application of various improvement efforts such as fertilization, liming, adding organic materials, implementing a planting system that follows the contour, and intensive terracing can increase the land suitability class to fairly suitable (S2).